Complications and Pathophysiology of COVID-19 in the Nervous System - Yu, Haiyang; Sun, Tong; Feng, Juan (Frontiers in Neurology, 2020)
The coronavirus disease (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has become a global public health threat. Majority of the patients with COVID-19 have fever, cough, and fatigue. Critically ill patients can develop dyspnea and acute respiratory distress syndrome. In addition to respiratory symptoms, neurological damage also occurs in some patients. However, the mechanisms by which SARS-CoV-2 invades the nervous system have not been elucidated yet. In order to provide some reference for designing optimal therapeutic strategies, we have discussed the complications and potential mechanisms of COVID-19 in the nervous system in this review.